1997
DOI: 10.1093/oxfordjournals.aje.a009327
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene and Myocardial Infarction Risk in the EURAMIC Study

Abstract: A multicenter case-control study was conducted to evaluate the relations between antioxidant status assessed by biomarkers and acute myocardial infarction. Incidence cases and frequency matched controls were recruited from 10 European countries to maximize the variance in exposure within the study. Adipose tissue needle aspiration biopsies were taken shortly after the infarction and analyzed for levels of carotenoids and tocopherols. An examination of colinearity including all covariates and the three caroteno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
181
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(193 citation statements)
references
References 29 publications
4
181
0
3
Order By: Relevance
“…The most powerful population-based evidence has been derived from a European multicentre case-control study (52) . This study investigated the relationship between acute myocardial infarction and adipose tissue antioxidant status.…”
Section: Carotenoids: Flavonoids: Cvd: Laser Doppler Imagingmentioning
confidence: 99%
“…The most powerful population-based evidence has been derived from a European multicentre case-control study (52) . This study investigated the relationship between acute myocardial infarction and adipose tissue antioxidant status.…”
Section: Carotenoids: Flavonoids: Cvd: Laser Doppler Imagingmentioning
confidence: 99%
“…In addition, a higher concentration of serum lycopene was inversely correlated with a decrease in the mean and maximal intima-mediated thickness of the common carotid artery (CCA-IMT) with low lycopene, resulting in an 18% increase in CCA-IMT (Rissanen et al, 2003). The European Multicenter Case-Control Study on Antioxidants, Myocardial Infarction and Breast Cancer Study (EURAMIC Study) reported that a higher lycopene concentration was independently protective against CVD (Kohlmeier et al, 1997). The Women's Health Study, further revealed that a decreased risk for developing CVD was more strongly associated with higher tomato intake than with lycopene intake (Sesso et al, 2003).…”
Section: A Basu and V Imrhanmentioning
confidence: 99%
“…Dietary intakes of tomatoes and tomato products containing lycopene have been associated with a decreased risk of diseases such as cancer and cardiovascular diseases (CVDs) in numerous studies (Kohlmeier et al, 1997;Giovannucci et al, 2002;Sesso et al, 2003). Tomatoes account for 85% of lycopene consumption in an average American diet, and is an essential component of the Mediterranean diet, which is well known for its cardioprotective and anticarcinogenic health effects (LaVecchia, 1997;de Lorgeril et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Biological interrelationships among carotenoids and various dietary antioxidants have been increasingly emphasized in the literature (37,(61)(62)(63) . That is why all our analyses were adjusted for other individual carotenoids.…”
Section: Discussionmentioning
confidence: 99%